Vasodilator efficiency of endogenous prostanoids, Ca²⁺-activated K⁺ channels and nitric oxide in rats with spontaneous, salt-dependent or NO-deficient hypertension - Behuliak, Michal; Pintérová, Mária; Kuneš, Jaroslav; Zicha, Josef (Hypertension research, 2011)
Hypertension is associated with the imbalance of vasoconstrictor and vasodilator systems. Vasodilation is usually evaluated in isolated blood vessels, but except for nitric oxide (NO), relatively little attention is given to the in vivo efficiency of particular vasodilator mechanisms. The aim of our study was to evaluate the contribution of endogenous vasodilator prostanoids, Ca(2+)-activated K(+) channels and NO to blood pressure (BP) maintenance in rats with three different forms of experimental hypertension. Both principal vasopressor systems (the renin-angiotensin system and the sympathetic nervous system) were blocked by captopril and pentolinium in conscious spontaneously hypertensive rats (SHRs), Dahl salt-hypertensive (DS-HS) rats and rats with NO-deficient hypertension, as well as in their normotensive controls. Thereafter, we monitored BP changes in rats subjected to either a sequential or an isolated blockade of prostanoid synthesis by the non-selective cyclooxygenase inhibitor, indomethacin, of Ca(2+)-activated K(+) channels by tetraethylammonium and of NO formation by N(G)-nitro-L-arginine methyl ester. All three forms of experimental hypertension were characterized by augmented sympathetic vasoconstriction. The vasodilatation exerted by endogenous prostanoids and Ca(2+)-activated K(+) channels was enhanced in all forms of hypertension, almost proportionally to BP elevation. On the contrary, NO-dependent vasodilatation was not enhanced in any form of experimental hypertension, and there was a severe relative NO deficiency in both, SHRs and DS-HS rats. In conclusion, our data suggested that there is a compensatory activation of vasodilator prostanoids and Ca(2+)-activated K(+) channels in rats with experimental hypertension, whereas NO-dependent vasodilatation is not augmented. Thus, the overall activity of vasodilator systems failed to compensate for augmented sympathetic vasoconstriction in hypertensive animals.
Keywords: hypertenze; potkani inbrední Dahl; potkani inbrední SHR; vazokonstriktory; Animals; kaptopril; oxid dusnatý; Prostaglandins; Nitric Oxide; krevní tlak; Rats, Inbred Dahl; prostaglandiny; Indomethacin; krysa rodu Rattus; Cyclooxygenase Inhibitors; Blood Pressure; Potassium Channels, Calcium-Activated; Rats; vazodilatace; Captopril; Rats, Inbred SHR; zvířata; Vasodilation; draslíkové kanály aktivované vápníkem; vazokonstrikce; Hypertension; Vasoconstrictor Agents; indomethacin; Vasoconstriction; inhibitory cyklooxygenasy